Productivity Growth and Job Creation in the Development Process of Industrial Clusters - Sonobe, Tetsushi; Higuchi, Yuki; Otsuka, Keijiro (World Bank, Washington, DC, 2013)
Poor management has long been suspected as a major constraint on job creation in the manufacturing sector in low-income countries. In this sector, countless micro and small enterprises in industrial clusters account for a large share of employment. This paper examines the roles of industrial clusters, managerial capacities, and entrepreneurship in improving productivity and creating jobs, by reviewing the literature and case studies, including recent experiments. We find that managerial capacities are major determinants of firms’ employment sizes and productivity growth, and that it is high innovative capacities, accompanied by high managerial capacities, that boost cluster-based industrial development.